What Drives Impulse Buying on Shopee? Exploring the Influences of Live Streaming, Online Trust, and e-WOM - Fadila, Nurul; Susilowati, Fitri; Sumarmi, Saptaningsih (Jurnal Ilmu Manajemen, 2025)
E-commerce is the largest contributor to the digital economy in Indonesia in 2023. One of the e-commerce that is the main choice for conducting online transactions is Shopee. Judging from the large number of consumers' interest in visiting Shopee, it allows consumers to carry out unplanned purchasing behavior or impulsive buying when visiting Shopee. This study aims to determine the influence of Live streaming, online customer trust, and electronic word of mouth on impulsive buying on the Shopee e-commerce platform. The research method was carried out by analyzing primary data by distributing questionnaires via Google Forms to 120 respondents in the Special Region of Yogyakarta. Data collection in this study was carried out in June 2024 in the Special Region of Yogyakarta. Respondents in this study were Shopee application users aged 18 years and over, domiciled in the Special Region of Yogyakarta, and had made unplanned product purchases on Shopee. The study utilized a purposive sampling method to select participants. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with the aid of SMARTPLS software version 4.1.0.3. The results of this study indicate that both live streaming and electronic word of mouth do not have a significant effect on impulsive buying. While online customer trust has a positive and significant effect on impulsive buying on the Shopee e-commerce platform.